Fertility preservation in women with cystic fibrosis pre‐lung transplantation: A mixed methods study. (21st November 2021) - Ladores, Sigrid; Campbell, Caitlin Marley; Bray, Leigh Ann; Li, Peng; Brown, Janet; Woods, Brittany; Corcoran, Jessica
Abstract: Aims: Explore the knowledge, experiences, preferences, and concerns related to fertility preservation as an option for building a biological family among women with cystic fibrosis. Design: Convergent mixed methods study design. Methods: We recruited women with cystic fibrosis of childbearing age in the United States through cystic fibrosis centres, snowball sampling, and social media. Participants completed an anonymous survey about fertility and fertility preservation ( n  = 50). We also conducted audio‐recorded, semi‐structured interviews with a subset of women to gain a better understanding of their perspectives ( n  = 20). We transcribed the interviews verbatim and analysed them using thematic analysis. Results: For the quantitative arm, 78% of women indicated that they would like to have a child in the future; however, 74% reported never having had conversations about fertility preservation with their providers. For the qualitative arm, four major themes emerged: (1) Women with cystic fibrosis have inadequate knowledge about fertility and fertility preservation; (2) fertility is a low priority area for the cystic fibrosis care team; (3) women with cystic fibrosis recommend that the cystic fibrosis care team provide specific fertility resources; and (4) providers and literature lack information on fertility and cystic fibrosis. Integrated findings identified that while the majority of women with cystic fibrosis want to become mothers in the future, including post‐lung transplantation, they have not received education on fertility preservation, and there is a general lack of knowledge on the topic of fertility in cystic fibrosis. Conclusion: Women with cystic fibrosis desire to have children but have little knowledge about fertility preservation, and cystic fibrosis providers do not initiate family planning discussions. Impact: Findings from the study support that additional education is needed for women with cystic fibrosis who are considering parenthood. Clinical care models should include early, regular, and thoughtful discussions about reproductive health issues, including fertility preservation.